2021
DOI: 10.1002/mp.14997
|View full text |Cite
|
Sign up to set email alerts
|

IMRT QA and gamma comparisons: The impact of detector geometry, spatial sampling, and delivery technique on gamma comparison sensitivity

Abstract: Purpose To separately quantify sensitivity differences in patient‐specific quality assurance comparisons analyzed with the gamma comparison for different measurement geometries, spatial samplings, and delivery techniques [intensity modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT)]. Methods Error‐free calculations for 20 IMRT and 20 VMAT cases were compared to calculations with known induced errors of varying magnitudes, using gamma comparisons. Five error types (MU scaling, three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“… 21 , 22 , 23 , 24 The chance of finding these errors is low using a diode‐array detector (e.g., ArcCHECK phantom) due to low detector density. 21 , 25 , 26 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 21 , 22 , 23 , 24 The chance of finding these errors is low using a diode‐array detector (e.g., ArcCHECK phantom) due to low detector density. 21 , 25 , 26 …”
Section: Methodsmentioning
confidence: 99%
“…It has been indicated that machine log file analysis is a robust and efficient way to detect errors originating from human mistakes, flawed planning, and data transfer problems 21–24 . The chance of finding these errors is low using a diode‐array detector (e.g., ArcCHECK phantom) due to low detector density 21,25,26 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a detector arrayʼs dosimetric characteristics and spatial resolution will also vary. For instance, p-type silicon diodes used by Delta 4 (Scandidos, Uppsala, Sweden) are spaced at 0.5 cm intervals in the central 6 × 6 cm 2 region, and 1 cm spacing outside the central area of the array 7 . The center spacing of adjacent ion chambers in the Octavius 729 detector array (PTW, Freiburg, Germany) is 1 cm, while the spacing of the Octavius 1500 detector array (PTW, Freiburg, Germany) is 0.707 cm 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, measured doses are compared to the TPS dose by calculating the γ pass rate and/ or reconstructing dose based on patientsʼ anatomical structures on CT images 6 . Because detector arrays such as ion chambers and semiconductors can provide the unambiguous interpretation on measurement dose and the ability to compare measurement to calculation within clinically meaningful accuracy thresholds, a variety of studies and products have been developed for extracting dose distributions on anatomical structures and verifying external beam radiation treatment plans with 2D or 3D detector arrays [7][8][9][10] . However, these data points exist only in discrete individual detectors.…”
mentioning
confidence: 99%